The impacts of climate changes on watershed streamflow and total dissolved nitrogen in Danjiang Watershed, China. Issue 1 (10th December 2022) - Liu, Yaxiu; Chen, Xinyu; Gao, Han; Sha, Jian; Li, Xue
Abstract: The impacts of future climate change on the watershed streamflow and total dissolved nitrogen (TDN) fluxes upstream of the Danjiang River were estimated. The newest shared socioeconomic pathways (SSP) in CMIP6 were used as a climate change scenario. The ensembles of downscaled GCM outputs from WorldClim were used as future climate change information. A combined modeling approach is proposed, including the Long Ashton Research Station Weather Generator (LARS-WG) model as a weather generator and the generalized watershed loading function (GWLF) model for watershed hydrochemical process model and scenario analysis. The results show that there is generally less annual streamflow but more annual TDN flux under future climate change scenarios. The monthly streamflow and TDN flux increased from May to July and decreased from August to October. Changes in streamflow and TDN fluxes were the greatest in the worst uncontrolled scenario of SSP 5-85, with a 12.1% decrease in annual streamflow in the 2070s and a 4.82% increase in annual TDN flux in the 2090s. This indicates that active climate policies can mitigate the impact of climate change on watersheds. Furthermore, the source apportionments of TDN from agricultural sources will increase to nearly 50% by the 2090s, and targeted management strategies should be implemented. HIGHLIGHTS: The newest CMIP6 climate change scenarios are used to estimate watershed responses. An approach for quick perspective of climate change impact on watershed is proposed. Positive climate policies can mitigate the impacts of climate change on watersheds. Graphical Abstract